2020
DOI: 10.1039/d0cy01371d
|View full text |Cite
|
Sign up to set email alerts
|

Platinum–palladium alloy nanotetrahedra with tuneable lattice-strain for enhanced intrinsic activity

Abstract: Understanding how to modify the intrinsic physical or chemical properties of precious metals to improve their electrocatalytic performance is crucial to the design of active and robust catalysts with high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Our simulations show that this is indeed the case for palladium (Pd). This suggests that the controlled preparation of alloyed or core-shell bimetallic tetrahedral nanocrystals are possible using the clean gas-phase plasma synthesis method, further increasing the tunability of Pt-based nanoparticles 26 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations show that this is indeed the case for palladium (Pd). This suggests that the controlled preparation of alloyed or core-shell bimetallic tetrahedral nanocrystals are possible using the clean gas-phase plasma synthesis method, further increasing the tunability of Pt-based nanoparticles 26 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…2A displays the crystalline and bimetallic properties of the as-prepared Pt n Co 100− n nanoalloy NWs structure. 45 The diffraction peaks observed for the Pt n Co 100− n nanoalloy NWs are located between that of pure Pt and Co, and are clearly indexed to face-centered cubic (fcc) Pt–Co alloy. The XRD data show that the Pt n Co 100− n /C nanoalloy catalysts are uniform in composition and there is no indication of phase segregation within the samples.…”
Section: Resultsmentioning
confidence: 99%
“…2A displays the crystalline and bimetallic properties of the as-prepared Pt n Co 100Àn nanoalloy NWs structure. 45 optimizes the oxygen-containing species (O ads ) adsorption strength to improve the ORR electrocatalytic activity. 46 The sizes, loading data, and compositions of the Pt n Co 100Àn /C nanoalloy catalysts are summarized in Table S1 (ESI †). )…”
Section: Morphology and Structure Of Nwsmentioning
confidence: 99%
“…Under the ligand effect, turning an appropriate balance between the oxygenated species and the adsorption of oxygen, is very meaningful for the excellent ORR activity. Chang et al reported distinguished enhancement of ORR activity and durability of the Pt-based nanowires (NWs) prepared by alloying Pd, Au, and Ni metal. Kong et al uncovered the ligand effect of the twisty PtFe NWs with a low content of Pt (<25%), exhibiting the highest mass activity3.4 A/mg Pt , which is ∼20 times higher, relative to the commercial Pt catalyst, and just ∼2% loss of activity after 40 000 cycles . Wu et al revealed ternary composition alloy catalyst of a highly durable PtPdCu by alloying PtPd (<50%) with copper base metal.…”
Section: Advanced Platinum-based Electrocatalystsmentioning
confidence: 99%